PIERCING THE CORPORATE VEIL DOCTRINE IMPLEMENTATION IN LIMITED COMPANY STOCKHOLDERS ACTIVITIES - Intihani, Siti Nur (Fakultas Hukum, Universitas Islam As-Syafi'iyah, 2022)
Research on the position of shareholders in Limited Liability Companies has been written by many legal experts and legal practitioners, in this study the author will examine how the application of the doctrine of piercing the corporate veil to the actions of shareholders and the legal consequences on Limited Liability Companies and the legal settlement process. The method used in this research is a normative juridical method (library study) by examining secondary data obtained from primary legal materials, namely regulations and court decisions, secondary legal materials, namely books, journals and research results from other parties and tertiary legal materials. namely dictionaries. The results of the study illustrate that the responsibilities of shareholders have been clearly regulated in Law Number 40 of 2007 concerning Limited Liability Companies (UUPT), namely in Article 3 paragraph (1) and paragraph (2). Article 3 paragraph (1) of the Company Law stipulates that the shareholders of the Company are not personally responsible for the agreements made on behalf of the Company and are not responsible for the Company's losses in excess of the shares owned. Article 3 paragraph (2) of the Company Law states that the liability of shareholders is no longer limited if the shareholders commit acts against the company. The unlawful act is that the shareholder concerned either directly or indirectly in bad faith utilizes the Company for personal interests, the shareholder concerned is involved in an unlawful act committed by the Company; or the shareholders concerned either directly or indirectly unlawfully use the Company's assets which results in the Company's assets being insufficient to pay off the Company's debts. The legal settlement of the actions of shareholders who violated the law in a Limited Liability Company has been rolled out in the Corruption Court, namely a case of corruption by the shareholders of PT. MP. The shareholder was charged with committing a criminal act of corruption in a protected forest area shooting project carried out by PT. MP and has been found guilty by the Central Jakarta District Court with a sentence of 2 years and a fine of money. At the level of appeal the decision became higher, namely 6 years and at the level of cassation the decision for 6 years has been upheld by the Supreme Court of the Republic of Indonesia. However, in its development, the doctrine of piercing the corporate veil was also applied to the actions of the Company's Directors and Commissioners who were negligent in running the Company.